2023
DOI: 10.1039/d3qo01227a
|View full text |Cite
|
Sign up to set email alerts
|

Advancement of vinylene carbonate as a coupling partner in metal-catalyzed C–H functionalization

Yicong Ge,
Qiang Yan,
Jiang Nan

Abstract: Organic carbonates are important and valuable building blocks in synthetic chemistry. Among them, vinylene carbonate (VC) has emerged as a promising coupling partner to participate in various attractive C-H conversions...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 89 publications
0
6
0
Order By: Relevance
“…Therefore, the reaction was then conducted using [Cp*RhCl 2 ] 2 (3 mol %) in dichloroethane (DCE) at 100 °C. But the corresponding product 3 a was isolated only in 33 % yield (entry b, Table 1), which was fully characterized using 1 H & 13 C NMR and mass spectrometry.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the reaction was then conducted using [Cp*RhCl 2 ] 2 (3 mol %) in dichloroethane (DCE) at 100 °C. But the corresponding product 3 a was isolated only in 33 % yield (entry b, Table 1), which was fully characterized using 1 H & 13 C NMR and mass spectrometry.…”
Section: Resultsmentioning
confidence: 99%
“…[12] It has been successfully utilized as a source of acetyl and acetylene to perform the [4 + 1] or [4 + 2] and [3 + 2] CÀ H annulation reactions. [13] Miura et al, reported, for the first time the vinylene carbonate as an oxidizing acetylene surrogate to carry out CÀ H annulation reactions using Rh(III) catalysis. [14] Subsequently, Zhang et al developed an oxidative annulations of vinylene carbonate with benzamides and acrylamides.…”
Section: Introductionmentioning
confidence: 99%
“…Seminal work reported by Miura and co-workers in 2019, which employed the Rh­(III) complex to facilitate the vinylene transfer event, initiated this chemistry (Figure B) . Thereafter, a number of vinylene transfer reactions catalyzed by Rh­(III), Ru­(II), and Co­(III) , were documented successively, providing a powerful toolbox to assemble small vinylene motifs to heterocyclic scaffolds that are otherwise difficult to be obtained by conventional methods (Figure C). , , …”
Section: Introductionmentioning
confidence: 98%
“…In the past few years, the transition-metal chemistry involving vinylene carbonate has witnessed a remarkable evolution. , In this context, vinylene transfer reactions by C–H activation delivering useful heterocyclic compounds gained extraordinary attention. Seminal work reported by Miura and co-workers in 2019, which employed the Rh­(III) complex to facilitate the vinylene transfer event, initiated this chemistry (Figure B) .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, signicant focus on the development of high heatresistant energetic materials has been observed due to their widespread applications in the military, civil, and aerospace elds. [1][2][3][4][5] In the synthesis of highly heat-resistant energetic materials, the balance between stability and energy is crucial. [6][7][8] Many conventional heat-resistant energetic materials oen exhibit inadequate energetic performance limiting their broad applicability and hindering the development of technology in the elds of national defense and aerospace.…”
Section: Introductionmentioning
confidence: 99%